בתעודות תדשות מסארי רזיקתם למקרא - Malamat, Abraham
אברהם מלמט; Prophetic Revelation in New Documents from Mari and the Bible; ARMT XIII 23.114.112.113; hebr. Fassung von 29:960; zusammen mit 26:d:1196 und 26:d:1197 wiederholt in 29:961.